LITERASI KEPADA MASYARAKAT DALAM PROGRAM PENCATATAN KEUANGAN SYARIAH MENGGUNAKAN MODUL MANAJEMEN KEUANGAN SYARIAH - Novianti, Serly; Zaharman, Zaharman; Arini, Arini; Trisno, Raymond; Margaretha S, Giovanny (Jurnal Pengabdian Kompetitif, 2024)
In this modern era, financial literacy has become a very important thing. Financial literacy is an alternative strategy for building economic growth and financial stability so that we can survive and face the various services available. The concept of sharia finance involves better financial management and selecting investments that are halal and profitable. The role of students in increasing sharia literacy is very important to socialize it to the community, which will ultimately be implemented by the community itself. Community service in the sharia financial recording program using the sharia financial management module. Provides an introduction to sharia accounting. This occurs due to a lack of socialization regarding sharia financial literacy, so that students have difficulty applying it in everyday life. Therefore, long-term socialization is needed so that students can understand it well.